Pemberdayaan Perempuan Berbasis Komunitas dalam Penguatan Agroindustri Gula Semut Kelapa Organik - Hidayat, Wahyu; Ningtyas, Devika Wahyu; Pamungkas, Febri; Haryanto, Budhi (Jurnal Dinamika Ekonomi Pembangunan, 2025)
The women-centered empowerment model developed by Kelompok Wanita Tani (KWT) Nira Lestari has been pivotal in transforming Magelang’s organic coconut palm sugar industry into a driver of rural economic development. Despite strong potential, the industry faces low generational renewal among sap tappers, limited technological resources, and strict export certification requirements. This qualitative study, based on interviews, observations, and documentation, analyzes how KWT Nira Lestari’s integration of the value chain from training to digital marketing and organic certification substantially increased production, strengthened women’s socio-economic roles, and opened export market access. The core argument is that empowering women through targeted, integrated interventions is key to industry sustainability. However, challenges remain, such as sap tapper regeneration, implementing e-traceability, and affording Hazard Analysis and Critical Control Points (HACCP) certification. The study recommends strengthening women-led incubators rooted in local resources, expanding digital and technical capacity, offering fiscal incentives, and promoting multi-stakeholder collaboration to build an inclusive, sustainable ecosystem.